Anti-inflammatory and antibacterial effects of kinos from Australian and Papua New Guinean Eucalyptus species - Mungkaje, Martha Yahimbu (Curtin University, 2015)
Kinos (astringent exudates) from Eucalyptus species are used by Indigenous Australians to treat inflammatory conditions and bacterial infections. ELISAs and Griess assay were used to investigate anti-inflammatory effect of kinos and flow cytometer for the phagocytic effect in murine RAW264.7 macrophages. Antibacterial effects of kinos were determined by agar diffusion and microdilution methods. The data demonstrate anti-inflammatory, phagocytic and antibacterial effect of kinos on mouse macrophages, thus substantiating some of the claims by traditional medicine.